Pengaruh Kualitas Layanan Terhadap Minat Nasabah Menggunakan Mobile Banking PT Bank Syariah Mandiri Surabaya - Fandi, Achmad (Universitas Negeri Surabaya, 2019)
The progress of information systems and technology has influenced the development of banking performance and is believed to be an attraction for customers. Bank Syariah Mandiri is one of the banks that has developed the m-banking service innovation, namely BSM Mobile Banking. This study aims to determine how much the influence of Mobile Banking Service Quality on Customer Interests of Bank Syariah Mandiri Surabaya. This study uses quantitative data and questionnaire dissemination. The method used is Non Probability Sampling with a sample of 120 respondents. Sampling technique with accidental sampling with several criteria and considerations. While the analytical method used is the T Test (Partial Test). Based on the test results indicate that there is an influence of service quality on the interest of customers using PT Bank Syariah Mandiri Surabaya mobile banking.